Birth Weights of the Babies in Diabetic Pregnancies - Alam, MJ; Mahmood, I; Selimuzzaman, ABM (TAJ: Journal of Teachers Association, 2009)
As the problem of diabetes is gradually increasing day by day, large babies of diabetic mothers are also becoming an alarming health problem. The shadow of diabetes falls on the pregnant women as long as fifteen or twenty years before the disease declares itself by glycosuria and hyperglycaemia. The latent interval between the birth of a large baby and the development of clinical diabetes may range up to 40 years, and the average as 24 years. During this period of prediabetics the mother may give birth to a series of large babies in her pregnancies. Pregnancy constitutes one of the few physiologic events that unmask the diabetic propensities. Excess fetal weight over 4 kg is regarded as fetal macrosomia and is due to fetal hyperglycemia; fetal pancreatic beta cell hyperplasia-foetal hyperinsullnism, deposition of fat and glycogen in foetus. Adequate control of diabetes with the preconception and prenatal care is the sheet anchor to prevent fetal macrosomia which occurs in 20-60% cases of gestational and clinical diabetes. TAJ 2009; 22(1): 311-314